Pendampingan Perancangan Desain Konten Instagram Produk Lokal Minyak Atsiri Laloka - Hartanti, Monica; Lukman, Christine Claudia (Jurnal Atma Inovasia, 2022)
Since Covid-19 impacted YSLH, one of the foundations engaged in the environment, income derived from training services and donations from well-wishers was greatly reduced. Luckily, with the Laloka Essential Oil (EO), income has potential to increase. The great advantage of Laloka EO is that it is affordable, seeing as this product uses raw Indonesian materials; another one of the advantages is the specialty of custom mixing essential oils with the skills of one of the YSLH’s volunteers who has previous pharmaceutical expertise. The needs of Laloka EO consist of online promotional media, especially during the COVID-19 pandemic. Using the Participatory Action Research (PAR) method, a team of lecturers and students from the Visual Communication Design of Maranatha University has helped Laloka EO volunteers, such as making some concept designs for Laloka EO’s Instagram content. This assistance is carried out online for three months. As a result of this assistance, Laloka EO is now accompanied with a design promoting concept in the social media, Instagram; but in terms of Instagram management, further efforts are needed. Currently, the problem is Laloka EO’s inability in accommodating permanent volunteers to manage its Instagram page on a routine schedule, resulting in irregular issued content designs.